Organizational behavior : an asian perspective - Griffin, Ricky W., author; Phillips, Jean M., author; Gully, Stanley M., author; Lim, Ghee Soon., adaptors; Chai, Audrey Wai Yin., adaptors; Wu, Pei Chuan., adaptors (Singapore : Cengage Learning Asia Pte, Ltd, 2019)
Includes bibliographical and references .